Pengaruh Periklanan Terhadap Keputusan Konsumen Untuk Membeli Di Alfamidi R.E Martadinata Manado - Grifilia L. Mokoagow; John A. F. Kalangi; Lucky F. Tamengkel (JURNAL ADMINISTRASI BISNIS, 2018)
This research is based on thinking on several factors that influence consumers decisionk to buy in retael dealers. With the growing efforts of the retael industry today the level of competition among retael industry is increasingly competitive, each dealer has a strategy in persuading the customers to choose and / or buy a items This activity was held at PT. Midi Utama Indonesia, Tbk. Branch Manado in order to know the relationship of these factors affect consumers to buy. Besides, this research is expected to be input to the leadership of PT. Midi Utama Indonesia, Tbk. Manado and is a contribution in marketing and advertising strategy. Data collection using the instrument in the form of questionnaires /interviews, observation and document studies, and for data analysis using quantitative methods. The results of this study to answer the hypothesis there is a significant relationship factors that influence consumers to buy, with a determinant responsibilities and proved research, which mean advertising strategy need to always innovated from time to time in order make consumers keep shoping on Alfamidi.Keywords: Advertising, Customer Behaviour